Sistema colinérgico central modula os ajustes dos sistemas cardiovascular e termorregulatório induzidos pelo exercício físico até a fadiga - Roberta Borges La Guardia (2007)
ABSTRACTThe purpose of this study was to verify if the cardiovascular andthermoregulatory adjustments mediated by central cholinergic receptors andperipheral cathecolamines during the physical exercise until fatigue. Wistar ratsweighting 278 ± 5 g, were submitted to bilateral adrenodemedullation (ADM) or sham(SHAM) surgery. After recovery, the animals were subjected to 3 additional surgeries:implantations of intracerebroventricular guide cannulae; of aortic catheter into leftcarotid and intraperitoneal implantation of thermal sensor. The animals were dividedinto 4 groups: SHAM or ADM groups submitted to exercise at 24 m/min and 5%inclination (~80% of VO2max) until fatigue, SHAM or ADM groups with no exercise.Each group received 2 experimental treatments: icv injection of 2 µL of 5 x 10-3 Mphysostigmine (FIS) or 0,15 M NaCl (SAL). Environmental temperature was 24,7 ±0,1ºC. No difference was found between groups or treatments in time to fatigue. InADM group the FIS increased exercise mean blood pressure (ADM-EX-SAL 16 ±4mmHg vs ADM-EX-FIS 33 ± 3mmHg, p<0,05). The intraperitoneal temperatureincreased in the ADM-EX group, but wasn´t different between the treatments (ADMEX-SAL 0,5 ± 0,1°C vs ADM-EX-FIS 0,5 ± 0,1°C). The tail temperature increased inthe ADM-EX-FIS group (ADM-EX-SAL 2,9 ± 0,6°C vs ADM-EX-FIS 4,1 ± 0,°C,p<0,05). No difference was found between ADM and SHAM. Heat loss andcardiovascular adjustments modulated by the central cholinergic receptors duringexercise are independ from the action of peripheral cathecolamines.